2006
DOI: 10.1177/0021955x06060944
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mechanical Vibration on Cell Density and Cell Morphology in the Dynamic Microcellular Foaming Process

Abstract: During the microcellular foaming extrusion process, the cell density in the foam could be increased by shear effects due to improved shear energy, which contributes to the free energy for bubble nucleation. However, the cells might also be deformed when the shear stress is high. In order to increase the cell density without destroying the cell structure, mechanical vibration induced by electromagnetic field is introduced into the foaming process. A novel electromagnetic dynamic foaming simulator has been desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…At the cellular level, MV leads to the changes of intracellular ion homeostasis [17,18], enzyme activities [19,20], cytoskeleton organization, cell shape [21], growth [22], division [23], proliferation [22], locomotion and survival. However, the cellular and molecular mechanisms of MV-induced biological effects on cells and organisms are not clear yet.…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular level, MV leads to the changes of intracellular ion homeostasis [17,18], enzyme activities [19,20], cytoskeleton organization, cell shape [21], growth [22], division [23], proliferation [22], locomotion and survival. However, the cellular and molecular mechanisms of MV-induced biological effects on cells and organisms are not clear yet.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Moreover, recent studies showed a close relationship between low-amplitude, high-frequency vibrations and growth of osteoprogenitor cells. [10][11][12] The interest in high-frequency vibration and its applications on bone growth is mainly caused by two factors. The first one is the growing awareness about the role that mechanical stimuli, involving bone tissue since its embryonic form, have in directing its development, so, in a biomimetic sense, the artificial reproduction of those biological conditions represents a viable approach.…”
Section: Introductionmentioning
confidence: 99%
“…During the foaming process, the plastic-gas mixture may experience a variety level of stresses inside the foam processing equipments, such as, extrusion or injection molding equipments. Previous researches showed that these stresses will induce cell nucleation and affect cell growth [37][38] [39], but the foaming mechanisms are still not thoroughly understood. To fill this gap, a device that allows for the in situ visualization of the foaming behaviours of polymer has been developed recently.…”
Section: Description Of the Perceived Needsmentioning
confidence: 99%